Study Of Voltage And Power Stability Margins Of Electrical Power System Using ANN - Marizan, Sulaiman (IET, 2016)
This paper presents the study of voltage and power stability margins of an electrical power system with the use of artificial neural network (ANN).Both voltage and power stability margins are obtained from the real power-voltage (PV) and reactive power-voltage (QV) curve.PV and QV curve are generated by a series of power flow with an incremental of loads for each power flow series.Then,an ANN based model will be used to predict the values of voltage and power stability margins.IEEE 30-bus system has been chosen as the electrical power system.The load flow analysis are simulated by using Power World Simulator software version 16.The ANN based model is developed using MATLAB.